Severe Left Ventricular Hypertrophy, Small Pericardial Effusion, and Diffuse Late Gadolinium Enhancement by Cardiac Magnetic Resonance Suspecting Cardiac Amyloidosis: Endomyocardial Biopsy Reveals an Unexpected Diagnosis - Hofmann, Nina P. (Case Rep Cardiol, 2016)
Left ventricular (LV) hypertrophy can be related to a multitude of cardiac disorders, such as hypertrophic cardiomyopathy (HCM), cardiac amyloidosis, and hypertensive heart disease. Although the presence of LV hypertrophy is generally associated with poorer cardiac outcomes, the early differentiation between these pathologies is crucial due to the presence of specific treatment options. The diagnostic process with LV hypertrophy requires the integration of clinical evaluation, electrocardiography (ECG), echocardiography, biochemical markers, and if required CMR and endomyocardial biopsy in order to reach the correct diagnosis. Here, we present a case of a patient with severe LV hypertrophy (septal wall thickness of 23 mm, LV mass of 264 g, and LV mass index of 147 g/m(2)), severely impaired longitudinal function, and preserved radial contractility (ejection fraction = 55%), accompanied by small pericardial effusion and diffuse late gadolinium enhancement (LGE) by cardiac magnetic resonance (CMR). Due to the imaging findings, an infiltrative cardiomyopathy, such as cardiac amyloidosis, was suspected. However, amyloid accumulation was excluded by endomyocardial biopsy, which revealed the presence of diffuse myocardial fibrosis in an advanced hypertensive heart disease.